2018
DOI: 10.1016/j.trsl.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of alternatively spliced GSN in head and neck squamous cell carcinoma

Abstract: We have recently performed the characterization of alternative splicing events (ASEs) in head and neck squamous cell carcinoma, which allows dysregulation of protein expression common for cancer cells. Such analysis demonstrated a high ASE prevalence among tumor samples, including tumor-specific alternative splicing in the GSN gene.In vitro studies confirmed that overall expression of either ASE-GSN or wild-type GSN (WT-GSN) isoform inversely correlated with cell proliferation, whereas the high ratio of ASE-GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…According to our results, the CASEs were significantly enriched in GO categories and KEGG pathways that were closely related to HNSC initiation or maintenance. More importantly, two AS events recently validated as functional in HNSC were also identified in our study 61, 63, which further confirms the suitability of RNA-Seq as a method to investigate AS changes in cancer. We also evaluated the 473 CASEs in an independent cohort.…”
Section: Discussionsupporting
confidence: 85%
“…According to our results, the CASEs were significantly enriched in GO categories and KEGG pathways that were closely related to HNSC initiation or maintenance. More importantly, two AS events recently validated as functional in HNSC were also identified in our study 61, 63, which further confirms the suitability of RNA-Seq as a method to investigate AS changes in cancer. We also evaluated the 473 CASEs in an independent cohort.…”
Section: Discussionsupporting
confidence: 85%
“…The investigation and clinical application of biomarkers is the key to prognosis assessment, molecular classification, grade determination, recurrence assessment, and early selection of appropriate therapeutics and means. According to the literature, the abnormal splicing level of the GSN gene is remarkably higher in tumor tissues than in para-carcinoma tissues and regulates the proliferation process of the HNSCC cell line (51). Meanwhile, the oncogene DOCK5 variant plays a critical role in the human papilloma virus (HPV)-negative HNSCC and is involved in tumor proliferation, migration, and invasion (52).…”
Section: Discussionmentioning
confidence: 99%
“…In the occurrence and development of HNSCC, epigenetic events play an important role, including DNA methylation, post-translational covalent modification of histones, chromatin remodeling and the effects of non-coding RNA (11)(12)(13)(14). Currently, an increasing number of splicing patterns have been found, such as the splicing variants of laminin subunit α3 (LAMA3), dystonin (DST), dedicator of cytokinesis (DOCK5), lysyl oxidase-like 2 (LOXL2) and gelsolin (GSN), and some studies have shown that these splicing variants can be used as cancer markers and potential therapeutic targets (15)(16)(17)(18). Some of these variants could even become novel antigens for specific targeted therapy of HNSCC, such as the splicing variant of GSN, which was reported to be able to serve as a biomarker of HNSCC and a neoantigen for HNSCC treatment (18).…”
Section: Introductionmentioning
confidence: 99%